Fried food consumption and risk of coronary artery disease: The Million Veteran Program. Issue 4 (April 2020) - Honerlaw, Jacqueline P.; Ho, Yuk-Lam; Nguyen, Xuan-Mai T.; Cho, Kelly; Vassy, Jason L.; Gagnon, David R.; O'Donnell, Christopher J.; Gaziano, J. Michael; Wilson, Peter W.F.; Djousse, Luc; ,
Summary: Introduction: Previous studies of the relationship between fried food consumption and coronary artery disease (CAD) have yielded conflicting results. We tested the hypothesis that frequent fried food consumption is associated with a higher risk of incident CAD events in Million Veteran Program (MVP) participants. Methods: Veterans Health Administration electronic health record data were linked to questionnaires completed at MVP enrollment. Self-reported fried food consumption at baseline was categorized: (<1, 1–3, 4–6 times per week or daily). The outcome of interest was non-fatal myocardial infarction or CAD events. We fitted a Cox regression model adjusting for age, sex, race, education, exercise, smoking and alcohol consumption. Results: Of 154, 663 MVP enrollees with survey data, mean age was 64 years and 90% were men. During a mean follow-up of approximately 3 years, there were 6, 725 CAD events. There was a positive linear relationship between frequency of fried food consumption and risk of CAD (p for trend 0.0015). Multivariable adjusted hazard ratios (95% CI) were 1.0 (ref), 1.07 (1.01–1.13), 1.08 (1.01–1.16), and 1.14 (1.03–1.27) across consecutive increasing categories of fried food intake. Conclusions: In a large national cohort of U.S. Veterans, fried food consumption has a positive, dose-dependent association with CAD.